Efficiency Through Automation: A Single System for Multiple Railway Guard Posts - Mochammad Hisam Zulwidad; Indah Sulistiyowati (Universitas Ahmad Dahlan, 2023)
One of the important factors in train travel is the guarding of railroad crossings. Unfortunately, the number of unguarded railway crossings is still quite large. This condition makes it prone to accidents, especially at crossings that are heavily traveled by vehicles. Most of the railway crossing guards in Indonesia use a manual system, where in this system one guard post can only guard one railway crossing, due to limited human resources from PT KAI, many railway crossing doors are not guarded. To reduce accidents and cover the lack of human resources from PT.KAI, an Efficiency tool through Automation was made: One System for Multiple Railway Crossing Guard Posts. This tool is equipped with several main components, namely PLC, HMI, Infrared Sensor, and servo motor. The crossing gate is fully controlled by PLC and HMI as a monitoring system for all components in real-time. By detecting the arrival of the train, the infrared sensor can work by utilizing the movement of the train passing the sensor, not only detecting the arrival of the train, the infrared sensor also works to give orders so that the Servo Motor as a crossing door can be immediately closed and opened on the miniature, the railroad crossing itself is also equipped with an infrared sensor that functions to detect the presence of vehicles in the middle of the railroad crossing controlled by PLC and HMI as a monitoring system. This tool has been tested and the device functions properly and can help reduce the accident rate at railroad crossings.